PENGARUH DAYA TARIK DAN KREDIBILITAS CELEBRITY ENDORSER DALAM IKLAN TELEVISI TERHADAP CITRA MEREK PRODUK SHAMPOO PANTENE DI KOTA PONTIANAK - admin, SILVIA ANJELINA B11111115 (Jurnal Manajemen Update, 2016)
This study aims to examine and analyze the effect of the attractiveness and credibility of the celebrity endorser in television advertising to the brand image of Pantene Shampoo products in Pontianak. This study consisted of brand image as the dependen variable attractiveness and credibility of the celebrity endorser as the independen variable. The population in this study is that female consumers who saw the adverstisement and use Pantene Shampoo in Pontianak. Total sampel are 100 respondents that selected by hypothesis whether the attractiveness and credibility of the celebrity endorser in television affect the brand image of Pantene Shampoo products in Pontianak. The results showed that the attractiveness of celebrity endorser give positif effect of brand image of Pantene Shampoo products in Pontianak with coefficient 0,035, with 0,000 significant value less tha 0,05, and credibility of celebrity endorser give positive effect to brand image of Pantene Shampoo product in Pontianak with coefficient 0,043, with 0,188 significant value less that 0,05. The result of determination coefficient (R2) is 0,610 which means the amount of influence exerted by the variable attractiveness and credibility celebrity endorser to brand image of Pantene Shampoo in Pontianak city is 61% while the rest 39% influenced by other factors. Keyword: Attractiveness, Credibility, Celebrity Endorser, Brand Image.